Social Action Through Mediascapes: Muslim Civil Society's Accountability Demands in BPKH Hajj Fund Governance Reporting via Indonesian Mainstream Media - Pambayun, Ellys Lestari; Fachrudin, Achmad; Iswandi, Andi; Sunarto, Sunarto; Djunaid, Jamaluddin (JURNAL INDO-ISLAMIKA, 2025)
This study explores the social actions of lecturers and students at PTIQ University Jakarta in responding to media news regarding the Hajj Financial Management Agency (BPKH). Using Weber's social action theory, the research emphasizes understanding the meaning behind individual actions, especially in media reception. Through interviews, focus group discussions (FGDs), and online engagement, the study identifies how Muslim audiences act critically and reflectively to verify, disseminate, and promote accurate information. Their efforts aim to counter public distrust and maintain institutional integrity. The findings highlight the role of Muslim social agents in shaping public discourse through ethical and constructive engagement with media. This phenomenon reflects a spiritual and value-driven orientation rooted in Islamic sociology, where social action is rational and guided by religious accountability. The study contributes to social action theory by integrating Islamic perspectives, emphasizing that social behavior in Muslim societies often reflects both worldly reasoning and ukhrāwī (afterlife) considerations.